Assemble a threat assessment team to prevent campus violence. Issue 7 (25th October 2019) - Rahn, Josh
Abstract : Rick Parfitt has been on the front lines of threat assessment for 20 years, with much of that time spent in higher education. Today, Parfitt is the Director of Safety and Security for Florida's Lee County School District. He's also the Florida Chapter President of the Association of Threat Assessment Professionals, a nationwide organization of people whose daily work involves threat assessment. Parfitt shared some of the key principles of threat assessment, suggesting how campus police departments can adopt this approach as the "standard of care" for identifying students or employees in crisis and preventing violent incidents.